2015
DOI: 10.5942/jawwa.2015.107.0079
|View full text |Cite
|
Sign up to set email alerts
|

Induced Genotoxicity in Nitrate‐Rich Water Treated With Medium‐Pressure Ultraviolet Processes

Abstract: Just as with chlorination, medium‐pressure (MP) ultraviolet (UV) treatment applied for disinfection purposes has been found to cause formation of genotoxic compounds, measured by the Ames test. By lowering the nitrate and dissolved organic carbon (DOC) content, the Ames test response was reduced substantially. The impact of nitrate photolysis on formation of genotoxic compounds was confirmed. A representative organic micro pollutant selection had no significant impact on the Ames test response. Formation of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The combination of UV with hydrogen peroxide (UV/H 2 O 2 ) is an advanced oxidation process (AOP) which has been shown to be a potential option to attenuate micropollutants in wastewater effluents. Formation of toxic byproducts is typically less of an issue for UV/H 2 O 2 , , although formation of mutagenic/genotoxic byproducts was recently reported after medium pressure UV/H 2 O 2 treatment of nitrate-containing waters. , Studies in clean water matrices (e.g., drinking water) have shown that UV/H 2 O 2 is energy-intensive due to the low UV absorption of H 2 O 2 , which results in low OH radical (·OH) formation efficacy. This is compounded by the high ·OH scavenging rate by wastewater matrix components such as dissolved organic matter (DOM) , and by the limited UV transmittance of conventionally treated wastewaters.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of UV with hydrogen peroxide (UV/H 2 O 2 ) is an advanced oxidation process (AOP) which has been shown to be a potential option to attenuate micropollutants in wastewater effluents. Formation of toxic byproducts is typically less of an issue for UV/H 2 O 2 , , although formation of mutagenic/genotoxic byproducts was recently reported after medium pressure UV/H 2 O 2 treatment of nitrate-containing waters. , Studies in clean water matrices (e.g., drinking water) have shown that UV/H 2 O 2 is energy-intensive due to the low UV absorption of H 2 O 2 , which results in low OH radical (·OH) formation efficacy. This is compounded by the high ·OH scavenging rate by wastewater matrix components such as dissolved organic matter (DOM) , and by the limited UV transmittance of conventionally treated wastewaters.…”
Section: Introductionmentioning
confidence: 99%
“…Several nitroaromatic compounds and nitrosamines are known to produce a response in the Ames test, 25,30,100 and multiple studies have shown that RNS reactions with DOM during UV irradiation result in the formation of nitrophenols and a simultaneous increase in the Ames response. 51,78,94,95,101 Similarly, genotoxicity increased and nitrated products formed in a full-scale MPUV/H 2 O 2 treatment process. 78 The contribution of specific nitr(os)ated products to the increased genotoxicity is unknown.…”
Section: Rns In Uv-based Water Treatment Processesmentioning
confidence: 99%
“…Oxidative processes are well-known for their possible creation of disinfection by-products, their formation also depends on process conditions and matrix properties such as nitrate and DOC content. [93][94][95]…”
Section: Treatment Processes Based On (Advanced) Oxidation Processesmentioning
confidence: 99%